rGO-TiO2-CdO-ZnO-Ag photocatalyst for enhancing photocatalytic degradation of methylene blue - Akyuz, Duygu (Elsevier, 2021)
Metal oxides are the most commonly used catalysts for removing different dyes and toxins. Multi metal oxide including catalysts (TiO2-CdO-ZnO) in presence of reduced graphene oxide (rGO) was synthesized by sol-gel method. The synthesized composite was loaded with silver nanoparticles (Ag). The wide band gap of TiO2 was decreased in presence of transition metal oxides. The photocorrosion of CdO decreased with the addition of ZnO and increased degradation efficiency. The synthesized catalysts were optimized and analyzed for methylene blue (MB) degradation in aqueous solution. Ultraviolet-visible (UV-Vis) absorption experiments were performed and rGO-TiO2-CdO-ZnO-Ag (3%) exhibited excellent degradation rate (15 min) with 91% degradation efficiency in UV light irradiation. In addition, this photocatalyst showed high photocurrent density, stability and recyclability.
Keywords: Dye degradation; Methylene blue; Reduced graphene oxide; Photocatalyst